2006
DOI: 10.1590/s1807-59322006000200003
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis Between Osteosarcoma and Ewing's Sarcoma: Evaluation of the Time From Onset of Signs and Symptoms Until Diagnosis

Abstract: OBJECTIVE: The purposes of this study were to describe the early signs and symptoms of osteosarcoma and Ewing's sarcoma, identify symptoms that could be used to help differentiate the two types of tumors, and determine the time elapsed between the onset of signs and symptoms and the definitive diagnosis in our service, providing information and imputus for earlier diagnosis of these tumors. METHODS: A retrospective analysis of the medical dossiers of 365 patients under 30 years of age diagnosed with osteosarco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
1
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 17 publications
5
21
1
5
Order By: Relevance
“…This study focused on the potential impact of two time intervals on the survival of children diagnosed with osteosarcoma who were treated in an LMIC. Our findings reveal that the median LD was longer than that observed in HIC and was comparable to reported times in other LMIC . Initial metastatic disease was found in 42.4% of patients; however, we failed to associate this finding with a delayed LD, which is similar to published data .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This study focused on the potential impact of two time intervals on the survival of children diagnosed with osteosarcoma who were treated in an LMIC. Our findings reveal that the median LD was longer than that observed in HIC and was comparable to reported times in other LMIC . Initial metastatic disease was found in 42.4% of patients; however, we failed to associate this finding with a delayed LD, which is similar to published data .…”
Section: Discussionsupporting
confidence: 87%
“…Our findings reveal that the median LD was longer than that observed in HIC 8,10,13,[23][24][25] and was comparable to reported times in other LMIC. 26,27 Initial metastatic disease was found in 42.4% of patients; however, we failed to associate this finding with a delayed LD, which is similar to published data. [8][9][10][11] An aggressive tumor biology was likely associated with rapid progression and advanced presentation.…”
Section: Discussionsupporting
confidence: 84%
“…The distal femur is a far more frequently affected site compared to the diaphyseal femur: 44% and 3%, respectively [2]. In terms of size, the lesion in the distal femur of our patient had progressed much more than the lesions in the fracture fragments (Figure 5B).…”
Section: Discussionmentioning
confidence: 69%
“…Guerra et al . [2] reported 20 such cases (11.4%) of 175 total patients in their series. The pathological nature of the fracture is commonly recognized on the basis of radiological signs.…”
Section: Introductionmentioning
confidence: 99%
“…15 Guerra et al showed that the patients with osteosarcoma or Ewing's sarcoma present local pain most frequently (89.5% of the time) as an early symptom. 9 The time interval between the onset of signs and symptoms and diagnosis observed for osteosarcoma was 5.25 months and Ewing's sarcoma it was 8.1 months. 9 According to review of literature the osteosarcoma and Ewing's sarcoma presenting symptoms are pain, swelling, weight loss, and pathological fracture.…”
Section: Discussionmentioning
confidence: 95%